Effect of ethanol extracts of some plants in inhibiting growth of Some fungi that cause Onion rot (Allium cepa L.) in the laboratory (Damascus University Journal of agriculture sciences, 2021)
This investigations carried out in 2019-2020, at Department of Plant Protection-Damascus University, to determine the antifungal activity of Ethanol extracts of leaves and flowers of Inula and leaves of Oregano, Melia azedarach and Eucalyptus, in inhibiting mycelium growth of fungi, Aspergillus niger, F. oxysporum, Botrytis cinerea isolated from onion (Allium cepa L.) on PDA in laboratory.The results showed that Ethano extracts of studied species gave significant inhibition to growth the tested fungi compared with the control. Ethanol extract of Inula and Oregano gave the superior inhibition effect to the A. niger  and F. oxysporum  fungi, where gave the median effective dose (EC50) values for inhibition of mycelial growth of fungi 365 and 462 ppm (Inula) and 456 and 617 ppm (Oregano) for two fungi, respectively.
Keywords: Plant extracts; Fungi; Onion